Human motion characteristics in relation to feeling familiar or frightened during an announced short interaction with a proactive humanoid - Baddoura, Ritta; Venture, Gentiane (Frontiers in Neurorobotics, 2014)
During an unannounced encounter between two humans and a proactive humanoid (called NAO), we study the dependencies between the human partners’ affective experience (measured via the answers to a questionnaire) particularly regarding feeling familiar and feeling frightened, and their arm and head motion (frequency and smoothness using Inertial Measurement Units (IMU)). NAO starts and ends its interaction with its partners by non-verbally greeting them hello (bowing) and goodbye (moving its arm). The robot is invested with a real and useful task to perform: handing each participant an envelope containing a questionnaire they need to answer. NAO’s behavior varies from one partner to the other (Smooth with X vs. Resisting with Y). The results show high positive correlations between feeling familiar while interacting with the robot and: the frequency and smoothness of the human arm movement when waving back goodbye, as well as the smoothness of the head during the whole encounter. Results also show a strong negative dependency between feeling frightened and the frequency of the human arm movement when waving back goodbye. The Principal Component Analysis (PCA) suggests that, in regards to the various motion measures examined in this paper, the head smoothness and the goodbye gesture frequency are the most reliable measures when it comes to considering the familiar experienced by the participants. The PCA also points out the irrelevance of the goodbye motion frequency when investigating the participants’ experience of fear in its relation to their motion characteristics. The results are discussed in light of the major findings of studies on body movements and postures accompanying specific emotions.